2007
DOI: 10.2807/esw.12.18.03187-en
|View full text |Cite
|
Sign up to set email alerts
|

A large outbreak of cryptosporidiosis in western Ireland linked to public water supply: a preliminary report

Abstract: In mid-February 2007, there was a small rise in the number of laboratory-notified cases of cryptosporidiosis in the city and county of Galway, Ireland in comparison to February 2006.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…For the wider community, the provision of efficiently and safely treated effluents and the subsequent stabilization of sewage sludge into pathogen-free biosolids is an important public health issue in Ireland and other countries. This is because both cryptosporidiosis outbreaks (Pelly et al 2007) and enteric pathogen surveys (Lucy et al 2008) have revealed Cryptosporidium contamination in the aquatic environment in Ireland (Skerrett and Holland 2000), in watersheds where land-spreading and wastewater discharge occurs (Council of the European Community, CEC, 1986, Council of the European Community, CEC, 1991). This presents a risk factor when these waters are used for drinking water abstraction or for recreational activities (Dorn et al 1985, Ingallinella et al 2002.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the wider community, the provision of efficiently and safely treated effluents and the subsequent stabilization of sewage sludge into pathogen-free biosolids is an important public health issue in Ireland and other countries. This is because both cryptosporidiosis outbreaks (Pelly et al 2007) and enteric pathogen surveys (Lucy et al 2008) have revealed Cryptosporidium contamination in the aquatic environment in Ireland (Skerrett and Holland 2000), in watersheds where land-spreading and wastewater discharge occurs (Council of the European Community, CEC, 1986, Council of the European Community, CEC, 1991). This presents a risk factor when these waters are used for drinking water abstraction or for recreational activities (Dorn et al 1985, Ingallinella et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…The European Union (EU) urban wastewater directive aims to protect the environment from the adverse effects of wastewater discharges; however, unfortunately, the relevant effluent quality requirements do not legislate for the presence of pathogens (Council of the European Community, CEC, 1986). Implementation of sewage sludge management has been introduced and implemented in the EU legislation (Council of the European Community, CEC, 1991) but research is needed into the safe practice of sewage sludge storage, treatment, and land-spreading to prevent contamination of watercourses, which can result in further epidemics (Pelly et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2004, several epidemics have been recorded in Ireland including a massive outbreak in Galway in 2007, with 182 clinically confirmed cases linked to drinking water; preliminary research indicated that both human sewage and animal wastes factored in the water contamination (Pelly et al 2007). Drinking-water outbreaks of cryptosporidiosis have been associated with heavy rainfall and flooding (Beach 2008).…”
Section: Discussionmentioning
confidence: 99%
“…On the 1 st January 2004, a new list of notifiable infectious diseases came into place [24] when cryptosporidiosis became a notifiable disease in all age groups and a requirement was introduced for confirmed cases to be reported. There was also an outbreak of cryptosporidiosis in Galway city in March 2007 which accounts for the notable increase in cases in that year [25]. …”
Section: Discussionmentioning
confidence: 99%